The (Anti-) Laptop Aesthetic. - Jaeger, Timothy (Contemporary Music Review, 2003)
This paper explores the use of French critic Pascal Beausse's and Jody Berland's descriptions of our contemporary moment to elaborate on the potential for reviving the twentieth-century avant-garde tradition of Cage and Kagel vis-à-vis Terre Thaemlitz in laptop performance.